The Immigration Policy and Process of European Integration: Supranationalism versus Intergovernmentalism? - Celal Polat (Ankara Avrupa Çalışmaları Dergisi)
The establishment of an immigration control system is closely connected with therealisation offree move ınent of persons. As freedom of movement of persons is designedfor the citizens of the EU, there is presently no right of free settlement for the ThirdCountry Nationals legally residing in one of the Member States.Immigration law is a highly politicised area of law and policy in all the MemberStates, being subject to constant change and amendment. With the current structure, theEU will not be capable to deal with the present and future developments in the field ofimmigration. It is clear that here is a need for regulation that goes further thenregulation on the national level. In principle supranational cooperation in this area isvery necessary.Immigration is a long-standing phenomenon, which must be understood withreference to its structural clauses and its global character. Intergovernmentalcooperation where the emphasis is laid by the sovereignty of the Member States seemsnot sufficient to solve the problem of the growth of immigration issues.This paper will focus on the development of the European Community'scompetence in immigration law. It will analyze whether immigration law is becomingsupranational and to what extent and in what way immigration policies are affected byEuropean integration.